Text Twigs - Bilda, Thomas; Landwehrjohann, Max (Satura, 2022)
THEOPHRASTUS OF ERESOS THE NATURAL HISTORY OF PLANTS VOL. 10: NOTES ON PLANTS DANGEROUS TO MAN THE YEAR HIPPODAMAS WAS ARCHON However, it now seems that there are plants on Earth with no other purpose than quiet, unstoppable self-reproduction. I was given an account of a peculiar shrub capable, with the deceptive allure of its Herculean size, of causing fire-like injuries to other living beings upon mere touch. Comparable to a silent army, this plant defends its territory with power and elegance. I would be thrilled to describe its leaves, blossoms, and fruits in more detail. Alas, there appears to be a limitation of unknown reason and constitution, set by nature itself.